2022
DOI: 10.5455/ovj.2022.v12.i6.23
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D inhibited endometriosis development in mice model through interleukin 17 modulation

Abstract: Background: Endometriosis is a common benign, estrogen-dependent, and chronic gynecological disease. Immune system disturbances and inflammatory abnormalities were involved in the pathogenesis of endometriosis. , Therefore, it is logical to use vitamin D, which has an immunomodulatory capacity, as supportive therapy for endometriosis. Aims: This research time to study the effect of different doses of vitamin D on IL-17 expression in endometriosis mice models. Methods: Endometriosis was induced in twenty-four m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…A total of 40 ICR mice (gender, female; age, 5 wk old; HFK Bio-Technology, Beijing, China) were randomly divided into the following four groups ( n = 10): the control group; the OHSS group; the OHSS + 16 IU VD3 group; and the OHSS + 24 IU VD3 group. To establish an OHSS mouse model, ovarian induction and VD3 administration were carried out as previously described by Jiang et al and Burjiah et al ( 2022 ) respectively. Mice in the control group were first subcutaneously injected with 10 IU pregnant mare serum gonadotrophin (PMSG).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 40 ICR mice (gender, female; age, 5 wk old; HFK Bio-Technology, Beijing, China) were randomly divided into the following four groups ( n = 10): the control group; the OHSS group; the OHSS + 16 IU VD3 group; and the OHSS + 24 IU VD3 group. To establish an OHSS mouse model, ovarian induction and VD3 administration were carried out as previously described by Jiang et al and Burjiah et al ( 2022 ) respectively. Mice in the control group were first subcutaneously injected with 10 IU pregnant mare serum gonadotrophin (PMSG).…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this study, the finding of another study revealed regression of endometrial implants as a result of vitamin D treatment in a rat model of endometriosis [ 195 ]. Vitamin D was found to prevent the development of endometriosis in mice by controlling interleukin-17 levels [ 196 ].…”
Section: The Role Of Vitamin D In the Pathogenesis Of Endometriosismentioning
confidence: 99%
“…Several of the conducted animal studies found vitamin D to reduce the size or volume of endometriotic lesions [ 44 , 45 , 46 ].…”
Section: The Role Of Selected Dietary Components In the Course Of End...mentioning
confidence: 99%
“…Furthermore, it has been noticed that vitamin D has the potential to interact with proinflammatory cytokines and other molecules intermediating in inflammatory processes. Thus, under the influence of vitamin D, the production of interleukin-17 (IL-17) [ 44 ] and IL-6 decreases [ 47 , 50 ]. Additionally, the experimental study conducted by Miyashita et al found that ectopic endometrial stromal cells (EESCs) incubated with 1,25-(OH) 2 D 3 were characterized with significantly lower amounts of IL-8, cyclooxygenase-2 (COX-2) mRNA, and prostaglandin E2 (PGE2) [ 48 ].…”
Section: The Role Of Selected Dietary Components In the Course Of End...mentioning
confidence: 99%
See 1 more Smart Citation